2017
DOI: 10.1590/1806-9061-2017-0463
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Induced Ascites in Broilers: Effects of Vitamin C and Coenzyme Q10

Abstract: We hypothesized that the supplementation of vitamin C (Vit. C) and coenzyme Q 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
1
8
0
3
Order By: Relevance
“…Another lipophilic compound, i.e., coenzyme Q, which interacts with the tocopheroxyl radical, regenerating its antioxidant form, can also participate in these cycles [ 54 ]. Moreover, significant data suggest that the antioxidant properties of coenzyme Q not only accompany but also complement the attributes of ascorbic acid [ 55 , 56 , 57 , 58 ]. However, so far it has not been possible to accurately describe their relationship.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…Another lipophilic compound, i.e., coenzyme Q, which interacts with the tocopheroxyl radical, regenerating its antioxidant form, can also participate in these cycles [ 54 ]. Moreover, significant data suggest that the antioxidant properties of coenzyme Q not only accompany but also complement the attributes of ascorbic acid [ 55 , 56 , 57 , 58 ]. However, so far it has not been possible to accurately describe their relationship.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…However, the quails' diet supplementation with CoQ 10 at a dose of 20 and 40 mg/kg diet eliminated the negative effects of CS, which was reflected in the increase in FBW and BWG, and in the decrease in liver weight. Some researchers have already shown the positive effects of the CoQ 10 addition into the diet on growth performance parameters (Fathi, 2015;Nemati et al, 2017;Kalantar et al, 2019), but others reported that CoQ 10 supplementation did not affect the FI in broilers exposed to CS (Nemati et al, 2017). It is well known that low ambient temperature effectively increases the energy requirement necessary for thermoregulation, which results in increased feed consumption in animals (Hangalapura, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Uma das explicações para a incidência da afecção é o aumento da produção de espécies reativas ao oxigênio, as ROS, e, por consequência do estresse oxidativo, antioxidantes importantes, como o ácido ascórbico, se encontram reduzidos no fígado e pulmões de aves de corte (NEMATI et al, 2017).…”
Section: Suplementação Vitamínicaunclassified
“…A suplementação de vitamina E, vitamina C, coenzima Q e outros antioxidantes beneficia animais ascíticos, visto que tais substâncias coletam as ROS e inibem suas reações deletérias sobre o organismo. A adição de vitamina C em doses de 500 ppm reduziu a mortalidade por ascite em ambientes frios, produzindo frangos de corte com performance melhor, menor nível plasmático de corticosterona e maior concentração sérica de T3 quando comparados a aves que não foram suplementadas (NEMATI et al, 2017;HASSNZADEH et al, 1997).…”
Section: Suplementação Vitamínicaunclassified